BEHAVIORAL FINANCE DALAM KEPUTUSAN INVESTASI: PERAN FOMO SEBAGAI MEDIASI - Gultom, Irena Nanda Febrina; Kamaludin, Kamaludin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
The gap between financial literacy and financial inclusion levels in Indonesia has fuelled irrational investor behaviour and led to the emergence of fear of missing out (FOMO). The emergence of FOMO has become a hot topic in the investment world recently. This study aims to measure the direct effect of availability bias, herding bias, loss aversion bias, and FOMO on investment decisions and test the role of FOMO as a mediator. The method used is quantitative with purposive sampling as the sampling technique. The respondent criteria set are investors who are actively trading shares in companies listed on the Indonesia Stock Exchange (IDX). A total of 230 questionnaires were collected and analysed using the Structural Equation Modeling (SEM) approach through the SmartPLS version 3 application. The research findings indicate that availability bias, herding bias, loss aversion bias, and FOMO have a positive and significant influence on investment decisions. Availability bias, herding bias, and loss aversion bias have a positive and significant effect on FOMO, and FOMO plays a partial mediating role in the relationship between availability bias, herding bias, and loss aversion bias with investment decisions.